Odpowiedzi

Najlepsza Odpowiedź!
2009-12-10T16:50:14+01:00
3x=12
x - y = 11

3x=12
x=11+y

3x(11+y)=12
x=11+y
2009-12-10T16:51:59+01:00
A)
3x = 12 / 3
x - y = 11

x=4
4-y=11

x=4
-y=11-4

x=4
-y=7 / (-1)

x=4
y=-7

b)
5y = 2 /5
x + y =2 ⅖

y=⅖
x+⅖=2⅖

y=⅖
x=2

c)
4y - x = 6
17y = 0/17

y=0
-x=6/(-1)

y=0
x=-6

d)
a = b
2a + b =9

a=b
3b=9 / 3

b=3
a=3
2009-12-10T16:52:45+01:00
A) 3x = 12/3
x - y = 11

x=4
y=-7

b) 5y = 2
x + y = 2 i 2/5

y=2/5
x=2

c) 4y - x = 6
17y = 0

y=0
x=-6

d) a = b
2a + b =9

3a=9
a=b=3